A contract design perspective on balancing the goals of utility regulation. (April 2021) - Eskesen, Anita
Abstract: Designing utility regulation involves trade-offs between different goals of contract design. Prioritising one objective may come at the cost of assigning a lower priority to another objective. This study compares four regulatory frameworks in terms of how they each prioritise different goals of contract design. While revenue-cap regulation can be said to minimise transaction costs, it also assigns a lower priority to coordination of production. Conversely, the frameworks that explicitly incorporate stakeholder engagement or negotiation prioritise coordination of production while assigning a lower priority to minimisation of transaction costs. Highlights: The paper gives a systematic coverage of four incentive regulations. Regulatory practices are compared to the theory of contract design. The practices prioritise the goals of contract design differently. The practices show how the focus on some goals leads to downgrading of others. A crucial tradeoff is between adjusting to demand and the cost of information rents.